Comparative study between 3-ports and 4-ports laparoscopic cholecystectomy for the cases of gall stone disease - KK Tamrakar (Society of Surgeons of Nepal, 2016)
Laparoscopic cholecystectomy is currently accepted approach for the management of patients with cholelithiasis. The standard method for removal of gall bladder in laparoscopic cholecystectomy is by using four ports. Although other techniques such as by using 3 ports or only single port are being practiced, their safety and efficacy has not been established. This study was done to assess the efficacy and safety of the use of only three ports for laparoscopic cholecystectomy.